2015
DOI: 10.5152/tjg.2014.6512
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-1 gene polymorphisms and Helicobacter pylori in gastroesophageal reflux disease

Abstract: Background/Aims: Our aim is to assess the relationship between interleukin 1β (IL-1 β), (-511,-31 alleles), interleukin 1RN (IL-RN), Helicobacter pylori (HP) status and gastroesophageal reflux disease (GERD) diagnosed by pH monitoring in the Turkish population. Materials and Methods: A Total of 100 consecutive patients with GERD were enrolled in the study. Genotypes of IL-1β (-511,-31), IL-1RN gene polymorphisms and HP status of the patients were analyzed. Results: While thirty-two patients were diagnosed as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…Although several studies have suggested that IL-1β -511 and IL-8–251 polymorphisms are associated with the development of various gastroduodenal disease including GERD [ 20 , 22 , 24 , 51 53 ], no statistically significant associations have been found between IL-1β -511 and IL-8–251 polymorphisms and GERD in this study. This result might be due to the small number of samples.…”
Section: Discussioncontrasting
confidence: 90%
“…Although several studies have suggested that IL-1β -511 and IL-8–251 polymorphisms are associated with the development of various gastroduodenal disease including GERD [ 20 , 22 , 24 , 51 53 ], no statistically significant associations have been found between IL-1β -511 and IL-8–251 polymorphisms and GERD in this study. This result might be due to the small number of samples.…”
Section: Discussioncontrasting
confidence: 90%
“…(15,20,21) The IL-1RN gene has been linked with a broad range of chronic inflammatory diseases and enhanced IL-1β secretion. (11,(22)(23)(24)(25)(26) The imbalance between IL-1 and IL-1ra has a crucial impact in developing inflammatory . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Comprising Il-1a Il-1b and Il-1rn Il-1rnmentioning
confidence: 99%
“…The correlation between IL-1B promoter polymorphisms and H. pylori infection has been studied previously in populations such as Turkish, Brazillian, and Italian. [11][12][13] For example, in meta-analysis studies, a strong synergistic interaction between IL-1β polymorphisms and H. pylori infection in the development of gastric cancer was detected. [14][15][16][17][18] In addition, an association between IL-1β polymorphisms and H. pylori infection was reported in Asian, European, and Latin American populations.…”
Section: Introductionmentioning
confidence: 99%